Estimation of heritability for nine common cancers using data from genome‐wide association studies in Chinese population. Issue 2 (11th October 2016) - Dai, Juncheng; Shen, Wei; Wen, Wanqing; Chang, Jiang; Wang, Tongmin; Chen, Haitao; Jin, Guangfu; Ma, Hongxia; Wu, Chen; Li, Lian; Song, Fengju; Zeng, YiXin; et al.
Abstract : The familial aggregation indicated the inheritance of cancer risk. Recent genome‐wide association studies (GWASs) have identified a number of common single‐nucleotide polymorphisms (SNPs). Following heritability analyses have shown that SNPs could explain a moderate amount of variance for different cancer phenotypes among Caucasians. However, little information was available in Chinese population. We performed a genome‐wide complex trait analysis for common cancers at nine anatomical sites in Chinese population (14, 629 cancer cases vs . 17, 554 controls) and estimated the heritability of these cancers based on the common SNPs. We found that common SNPs explained certain amount of heritability with significance for all nine cancer sites: gastric cancer (20.26%), esophageal squamous cell carcinoma (19.86%), colorectal cancer (16.30%), lung cancer (LC) (15.17%), and epithelial ovarian cancer (13.31%), and a similar heritability around 10% for hepatitis B virus‐related hepatocellular carcinoma, prostate cancer, breast cancer and nasopharyngeal carcinoma. We found that nearly or less than 25% change was shown when removing the regions expanding 250 kb or 500 kb upward and downward of the GWAS‐reported SNPs. We also found strong linear correlations between variance partitioned by each chromosome and chromosomal length only for LC ( R 2 = 0.641, p = 0.001) and esophageal squamous cell cancer ( R 2 = 0.633, p = 0.002), which implied us the complex heterogeneity of cancers. These results indicate polygenic genetic architecture of the nine common cancers in Chinese population. Further efforts should be made to discover the hidden heritability of different cancer types among Chinese. Abstract : What's new? Almost every cancer exhibits familial aggregation. Here, the authors conducted a genome‐wide complex trait analysis in Chinese participants in previous genome‐wide association studies to estimate heritability explained by single‐nucleotide polymorphisms for nine common cancers (gastric, esophageal, colorectal, lung, ovarian, hepatocellular, prostrate, breast, and nasopharyngeal). The explained heritability ranged from 10.19% to 20.26% indicating a polygenic architecture of all examined cancer types. The authors recommend performing even larger studies to better analyze the hidden heritability of each cancer type.